Klimatförändring och Norden : Regionala konkretiseringsexempel på 50-100 års sikt - Rummukainen, M. ; 0000-0001-5709-9804 (Terra, 2001)
Assessments of the possible future climate change, driven by anthropogenic emissions of greenhouse gases, are made with global climate models. These describe the large-scale features rather than regional details of climate, such as variations due to mountains, lakes, and inland oceans. Regional climate modelling improves the details in climate projections. Examples for the Nordic region illustrate that for a given global mean temperature rise, the regional temperature changes appear larger, changes in precipitation and water availability can vary widely within the region, and local processes modify changes, e.g., in the wind climate and the ocean climate of the Baltic Sea.